Flowable 2D textile structures for the production of thermoplastic 3D FRP parts with continuous fiber reinforcement between shell and rib - Hellmann, Sven; Overberg, Matthias; Pham, Minh Quang; Häntzsche, Eric; Gereke, Thomas; Cherif, Chokri (Wydawnictwo Politechniki Łódzkiej, 2022)
Nature shows evolutionary fiber-reinforced solutions, e.g. a peanut shell that enables a high stiffness with extremely low component masses by using complex shell and rib arrangements. Lightweight shellshaped components made of fiber-reinforced plastic (FRP) are often stiffened with ribs. In this work, a new method is proposed to produce directional fiber reinforcement in the transition area from shell to rib and within the rib by a direct thermal pressing process. Numerical calculations are initially used to demonstrate the potential of this type of structure. The source material is a flowable 2D textile hybrid structure consisting of continuous glass fibers and discontinuous recycled carbon fibers. The arrangement of the fibers leads to a defined flow movement of matrix and fibers and thus the production of a 3D FRP component with continuous fibers in the shell area and staple fiber-based reinforcement in the rib area and in between.
Keywords: continuous fiber reinforcement; FRP; hybrid yarns; recycled carbon fibers; thermoplastic composites; fiber-reinforced plastic; wzmocnienie włóknami ciągłymi; tworzywo sztuczne wzmocnione włóknem; przędze hybrydowe; włókna węglowe pochodzące z recyklingu; kompozyty termoplastyczne